Safety and efficacy of a novel three-step anti-acne regimen formulated specifically for women - Timothy Falla, PhD; Katie Rodan, MD; Kathy Fields, MD; Danielle Ong, BS; Cezary Skobowiat, DVM, PhD, ScD (Wolters Kluwer, 2020)
Background: Due to ambient environmental- and lifestyle-associated stressors, the prevalence of acne in adult women has been increasing. Classical anti-acne treatments using benzoyl peroxide technology are associated with dehydration of the skin, which may accelerate aging and further reduce treatment compliance. The addition of bio-functional actives intended to replenish hydration and improve barrier function may hasten the onset of anti-acne benefits while restoring a healthy appearance and counteracting skin aging effects. Objective: The objective of this study was to test the safety and efficacy of a new three-step topical anti-acne regimen designed specifically to improve the overall condition and appearance of the skin in women with acne. Methods: Safety and efficacy were tested in an 8-week study of women ages 22 to 44 years with mild to moderate acne. Skin endpoints were monitored at baseline and weeks 1, 4, and 8 by clinical grading, measurement of sebum secretion using a sebumeter, standardized pictures, and self-validation questionnaires. Results: A total of 31 women completed the study. Acne severity and lesion counts, including comedones and papules, improved gradually starting from week 1 and continued to improve throughout the study period, reaching statistical and clinical relevance at weeks 4 and 8. Moreover, significant improvements in skin roughness, radiance, overall healthy appearance, and oiliness (further confirmed with decreased sebum production) were observed. Compared with baseline responses, participants reported noticeable improvements in acne lesions and overall healthier-looking skin. Participants also noticed overall younger-looking skin at the end of the study period. Conclusion: This three-step regimen provided efficacious anti-acne benefits to the skin that were also gentle, safe, and well tolerated.